The Crary Fan: A trough-mouth fan on the Weddell Sea continental margin, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve (Marine Geology, 1991)
Multichannel seismic investigations show the presence of a large trough-mouth fan deposit on the continental margin in the southern Weddell Sea. A characteristic feature of the fan is relatively few, but large canyons and/or channels which appear to have been stable for long periods. Levees associated with the channels may reach thicknesses of more than 1 km. Drilling during ODP Leg 113 recorded the presence of glaciers in East Antarctica since early Oligocene time, and the seismic stratigraphic evidence suggests that the submarine fan is largely composed of glacigenic sediments. The channel-levee systems and complexes indicate several growth phases, apparently controlled by glacial/interglacial climate fluctuations, with maximum fan growth during glacial periods. The present interglacial period is characterized by strong and erosive flow of Ice Shelf Water running down the western slope of the fan and carrying only minor amounts of suspended matter. The fan is essentially sediment starved during interglacial periods. The dimensions of the channel-levee complexes and the persistent loci of sediment supply suggest that turbidite sedimentation resulted from melting of wet-based glaciers at or near the shelf edge, which has consequently prograded 70-80 km seaward.
Keywords: Sørishavet; Weddellhavet; havbunnen; isshelf; kontinentalmargin; kontinentalsokkel; marin geologi; seismologi

Geophysical evidence for the East Antarctic plate boundary in the Weddell Sea - Kristoffersen, Yngve; Haugland, Kristen (Nature, 1986)
An improved Gondwanaland reconstruction compatible with geological and geophysical information from the surrounding oceans and continents seems to require microplates to solve the enigmatic pre-early-Mesozoic tectonic relation between West and East Antarctica1. New multi-channel seismic reflection data from the southeastern Weddell Sea acquired during the 1984–85 Norwegian Antarctic Research Expedition (NARE) have outlined a linear WSW–ENE-trending basement ridge buried below the continental slope over a distance of 700 km. This structural high truncates the trend of the large sedimentary basins below the Filchner and Ronne ice shelves and may continue to within a few hundred kilometres of the Antarctic Penninsula. We interpret the basement ridge as part of the East Antarctic plate boundary during the break-up of Gondwana. The morphology and structure of this boundary show greater apparent similarity to a rifted or obliquely rifted margin than to the sheared margin which is predicted by current reconstructions2,3. A linear East Antarctic plate margin extending to the vicinity of the Antarctic Peninsula makes any post-rift micro-plate motion in the Weddell Embayment unlikely.
Keywords: Antarktis; NARE 1984/85; Weddellhavet; geofysikk; geologi; tektonikk

Geology, geophysics, and hydrocarbon potential of Antarctica continental margin of Weddell Sea - Hinz, K.; Kristoffersen, Yngve (AAPG Bulletin, 1987)
A prominent escarpment, called the Explora-Andenes Escarpment, has been recognized between long. 40°W, lat. 72°40^primeS and long. 10°W, lat. 69°20^primeS. It separates the continental margin from the Weddell Sea basin. Our recent MCS data have revealed the presence of some remarkably symmetric structures beneath a thick pile of tectonically undisturbed sediments. For example, two extensive wedge-shaped basement units occur between 20°W and 40°W. These units are characterized by a pattern of divergent reflectors which surround an elongated depression in basement. The northern wedge terminates against the Explora-Andenes Escarpment between 25°W and 30°W. The southern wedge, known as the Explora Wedge, shows a northward-dipping reflection pattern. The seismic characteristics suggest that both wedges consist of volcanic rocks. The basement depression is interpreted as a failed rift basin. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of "dipping reflectors." The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of dipping reflectors. The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures.
Keywords: Antarktis; Sørishavet; Weddellhavet; geofysikk; geologi

Marine geological studies on the Weddel Sea shelf - Solheim, Anders; Kristoffersen, Yngve (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; marin geologi

Geophysical studies in the southern Weddell Sea - Haugland, Kristen; Kristoffersen, Yngve (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; geofysikk

Shelf progradation on a glaciated continental margin, Queen Maud Land, Antarctica - Kristoffersen, Yngve; Winterhalter, Boris; Solheim, Anders (Marine Geology, 2000)
A detailed survey of the continental margin in the eastern Weddell Sea demonstrates shelf progradation by material input from discrete glacial wedges that amalgamate to form the present near rectilinear shelf edge. Kvitkuven Ice Rise is located between two trough mouth fans and rests on a thick sediment substratum that predates the shelf sequences north of it. Shelf progradation, west of the ice rise, preceded the progradation east of it. In this way the seaward progression of a shelf edge may reflect the broad scale expansion of the East Antarctic Ice Sheet, but the timing of shelf progradation can be different in adjacent areas. The progradational glacial wedges on the continental shelf mapped by this survey are correlated stratigraphically to be within the post Late Miocene glacial sequence, drilled at ODP Site 693 on the middle continental slope 200 km to the northeast. Two submarine moraine ridge complexes on the shelf parallel the shelf edge. A radiocarbon age of 18:950 ^ 280 years BP from the front of the inner complex (water depth 319 m) suggests that grounded ice at most reached the present mid-shelf area in front of the ice rise during the Late Wisconsin Glacial Maximum, or had retreated to this position at that time.
Keywords: Dronning Maud Land; Weddellhavet; marin geofysikk; marin geologi; oseanografi; seismisk stratigrafi

Seismic investigations in the Weddell Sea Embayment - Haugland, Kristen; Kristoffersen, Yngve; Velde, Anders (Tectonophysics, 1985)
Keywords: Antarktis; NARE 1976/77; NARE 1978/79; Weddellhavet; ekspedisjoner; seismologi

Improved Seismic Stratigraphy of the Mesozoic Weddell Sea - Rogenhagen, Johannes; Jokat, Wilfried; Hinz, Karl; Kristoffersen, Yngve (Marine Geophysical Researches, 2004)
We present a compilation of more than 45,000 km of multichannel seismic data acquired in the last three decades in the Weddell Sea. In accordance with recent tectonic models and available drillhole information, a consistent stratigraphic model for depositional units W1–W5 is set up. In conjunction with existing aeromagnetic data, a chronostratigraphic timetable is compiled and units W1.5, W2 and W3 are tentatively dated to have ages of between 136 Ma and 114 Ma. The age of W3 is not well constrained, but might be younger than 114 Ma. The data indicate that the thickest sediments are present in the western and southern Weddell Sea. These areas formed the earliest basins in the Weddell Sea and so the distribution of Mesozoic sediments is in accordance with the tectonic development of the ocean basin. In terms of Cenozoic glacial sediments, the largest depocenters are situated in front of the Filchner–Ronne Shelf, i.e. at the Crary Fan, with a thickness of up to 3 km.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi; seismologi; stratigrafi; tektonikk

Pilot shallow drilling on the continental shelf, Dronning Maud Land, Antarctica - Kristoffersen, Yngve; Strand, Kari; Vorren, Tore; Harwood, Dave; Webb, Peter (Antarctic Science, 2000)
A light, mining drill rig deployed from the stern of a research vessel has been used to carry out shallow drilling in 212 m water depth on the continental shelf in the eastern Weddell Sea. Penetration was 15 m below the seabed with 18% recovery in the 31 hours available for the experiment. The recovered glacigenic sediments are predominantly volcanic material of basaltic and andesitic composition with petrological characteristics and age similar to the continental flood basalts exposed in Vestfjella, about 130 km upstream from the drill site. The sediments include a reworked marine Miocene diatom flora. The material documents oscillations of the East Antarctic Ice Sheet over the past 30 ka. The lowermost diamicton probably represents a deformation till, and the grounding line retreated past the drill site 30 km from the shelf edge about 30 kyr BP. A readvance occurred during the Late Wisconsin Glacial Maximum. Assuming a reservoir correction of 1300 yr, marine conditions existed at the site between 10.1-7 kyr BP, and later at least between 2.8 and 2.5 kyr BP. The stratigraphy at the site has been disturbed by iceberg ploughing and/or contact between the ice shelf and the sea floor during local advances after 2.5 kyr BP.
Keywords: Dronning Maud Land; Weddellhavet; geokjemi; geologi; glasiologi; havbunnen; innlandsis; isshelf; kontinentalsokkel; stratigrafi

Input of Glaciomarine Sediments along the East Antarctic Continental Margin; Depositional Processes on the Cosmonaut Sea Continental Slope and Rise and a Regional Acoustic Stratigraphic Correlation from 40° W to 80° E - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, V; Kudryavtsev, Genadii (Marine Geophysical Researches, 2004)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes in the continental slope and rise area. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents, which redeposited the sediments into a large scale drift deposit prior to the main glaciogenic input along the margin. High-relief semicircular or elongated depositional structures are also found on the upper continental rise stratigraphically above the regional sediment lens, and were deposited by the combined influence of downslope and alongslope sediment transport. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of downslope turbidity transport and westward flowing bottom currents after initiation of glacigenic input to the slope and rise. We compare the seismostratigraphic signatures along the continental margin segments of the adjacent Riiser Larsen Sea, the Weddell Sea and the Prydz Bay/Cooperation Sea, focussing on indications that may be interpreted as a preglacial-glaciomarine transition in the depositional environment. We suggest that earliest glaciogenic input to the continental slope and rise occurred in the Prydz Bay and possibly in the Weddell Sea. At a later stage, an intensification of the oceanic circulation pattern occurred, resulting in the deposition of the regional plastered drift deposit along the Cosmonaut Sea margin, as well as the initiation of large drift deposits in the Cooperation Sea. At an even later stage, possibly in the middle Miocene, glacial advances across the continental shelf were initiated along the Cosmonaut Sea and the Riiser Larsen Sea continental margins.
Keywords: Sørishavet; Weddellhavet; marin geofysikk; marin geologi; oseanografi

Timing of glacial events in Antarctica - diamond drilling into the glaciomarine sequence of the Weddell Sea continental shelf - Koç, Nalân; Kuvaas, Berit; Kristoffersen, Yngve; Hansen, Erik; Persson, Allan (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; glasiologi; kontinentalsokkel; sedimenter; sedimentologi; seismologi

Reconstruction of changes in the Weddell Sea sector of the Antarctic Ice Sheet since the Last Glacial Maximum - Hillenbrand, Claus-Dieter; Bentley, Michael J.; Stolldorf, Travis D.; Hein, Andrew S.; Kuhn, Gerhard; Graham, Alastair G.C.; Fogwill, Christopher J.; Kristoffersen, Yngve; Smith, James. A.; Anderson, John B.; Larter, Robert D.; Melles, Martin; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
The Weddell Sea sector is one of the main formation sites for Antarctic Bottom Water and an outlet for about one fifth of Antarctica's continental ice volume. Over the last few decades, studies on glacial–geological records in this sector have provided conflicting reconstructions of changes in ice-sheet extent and ice-sheet thickness since the Last Glacial Maximum (LGM at ca 23–19 calibrated kiloyears before present, cal ka BP). Terrestrial geomorphological records and exposure ages obtained from rocks in the hinterland of the Weddell Sea, ice-sheet thickness constraints from ice cores and some radiocarbon dates on offshore sediments were interpreted to indicate no significant ice thickening and locally restricted grounding-line advance at the LGM. Other marine geological and geophysical studies concluded that subglacial bedforms mapped on the Weddell Sea continental shelf, subglacial deposits and sediments over-compacted by overriding ice recovered in cores, and the few available radiocarbon ages from marine sediments are consistent with major ice-sheet advance at the LGM. Reflecting the geological interpretations, different ice-sheet models have reconstructed conflicting LGM ice-sheet configurations for the Weddell Sea sector. Consequently, the estimated contributions of ice-sheet build-up in the Weddell Sea sector to the LGM sea-level low-stand of ∼130 m vary considerably. In this paper, we summarise and review the geological records of past ice-sheet margins and past ice-sheet elevations in the Weddell Sea sector. We compile marine and terrestrial chronological data constraining former ice-sheet size, thereby highlighting different levels of certainty, and present two alternative scenarios of the LGM ice-sheet configuration, including time-slice reconstructions for post-LGM grounding-line retreat. Moreover, we discuss consistencies and possible reasons for inconsistencies between the various reconstructions and propose objectives for future research. The aim of our study is to provide two alternative interpretations of glacial–geological datasets on Antarctic Ice-Sheet History for the Weddell Sea sector, which can be utilised to test and improve numerical ice-sheet models.
Keywords: Antarctica; Cosmogenic nuclide surface exposure age dating; Deglaciation; Geomorphology; Glacial history; Ice Shelf; Ice sheet; Last Glacial Maximum; Radiocarbon dating; Sea level; Sørishavet; Weddellhavet; geologi; geomorfologi; glasiologi